Después del manicomio - Villa-Palomino, Julio; Shimabukuro Higa, Alexandra Hiromi; Cornejo Rossello, Guillermo Percy (Pontificia Universidad Católica del Perú, 2024)
This article explores Peru’s transition towards community mental health from 1980 to 2022. Using an approach from medical anthropology and related social sciences, we argue that the community mental health reform in Peru has been influenced and shaped by multiple sociohistorical and political processes such as the period of internal armed conflict, economic crises, and the adoption of neoliberal policies. This article is based on an analysis of the national guidelines and reports related to mental health, participant observation in a Community Mental Health Center and with residents of a district of Lima, and interviews with citizens, health providers, and mental health activists. The analysis of the national mental health guidelines shows how sociohistorical processes influence mental health policies. The ethnographic work complicates citizens’ varying perceptions of the community mental health model and the process of psychiatric deinstitutionalization. Now that mental health care takes place in the community, our ethnographic analysis points to changes in different notions of madness, care, and mental health and illness. The mental health reform also generates opportunities, such as mental health activism and the potential inclusion of community actors, as well as the inclusion of people with mental health problems in the elaboration of their diagnoses and treatments.

Este artículo explora la transición hacia la salud mental comunitaria en el Perú desde 1980 hasta el 2022. Usando una aproximación desde la antropología médica y ciencias sociales afines, argumentamos que la reforma en salud mental comunitaria en el Perú ha sido influenciada y modelada por múltiples procesos sociohistóricos y políticos como el periodo de conflicto armado interno, crisis económicas y la adopción de políticas neoliberales. Esta investigación se basa en un análisis de los diferentes lineamientos, reportes y normas técnicas referidas a la salud mental, observación participante en un Centro de Salud Mental Comunitario y con residentes de un distrito de Lima Metropolitana, y entrevistas con ciudadanos y proveedores de salud. El análisis de los lineamientos evidencia los distintos procesos sociohistóricos que influyen sobre las políticas de salud mental en el país. Los hallazgos etnográficos complican las distintas percepciones que tienen los ciudadanos del modelo de salud mental comunitaria y el proceso de desinstitucionalización. Ahora que el cuidado de la salud mental se realiza en la comunidad, nuestro análisis etnográfico señala los cambios en las distintas nociones que se tienen sobre locura, ciudado y salud y enfermedad mental. La reforma en salud mental también genera oportunidades, como el activismo en salud mental y la potencial inclusión de actores comunitarios, así como de personas con problemas de salud mental en la elaboración de sus diagnósticos y sus tratamientos.
After the Asylum
Keywords: Mental Health; Community Mental Health; Health Reform; Care; Peru; Salud Mental; Salud Mental Comunitaria; Reforma de salud; Cuidado; Perú; https://purl.org/pe-repo/ocde/ford#5.04.03